Construct Validation with Rasch Modeling of Pedagogical Literacy Measurement Instrument for Teachers in Junior High School Environment - Rahmi, Kholifatun Nisa; Susongko, Purwo; Suriswo, Suriswo (Journal of English Language and Education, 2025)
This study aims to develop and analyze a pedagogical literacy assessment instrument in the junior high school environment using the Rasch modeling. In this research, the development and analysis of the instrument involved an approach consisting of content, substantive, structural, and consequential aspects. The pedagogical literacy assessment instrument was developed based on ten teacher competency standards according to the Indonesian Ministry of National Education Regulation No. 16 of 2007, presented in the form of multiple-choice questions, totaling 60 items. This study is a Research and Development (RD) with a research design using ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research approach used is mixed methods, which combines both qualitative and quantitative forms. Data was collected from 122 teachers across four schools: SMPN 7 Tegal City, SMPN 14 Tegal City, SMPN 17 Tegal City, and SMPN 19 Tegal City. The results of data analysis using the Rasch model on R programming version 4.03 with the eRm package showed that 88% of the items were valid with a p-value 0.05. The validation results, which cover content, psychometrics, and constructs (content, substantive, structural, and external), met the requirements for being considered good items.